Effects of cyclic voltammetric scan rates, scan time, temperatures and carbon addition on sulphation of Pb disc electrodes in aqueous H2SO4. (23rd February 2020) - Zhu, Hua; Li, Yang; Song, Yuqiao; Zhao, Guangjin; Wu, Wenlong; Zhou, Shoubin; Wang, Dihua; Xiao, Wei
Abstract: Herein, we aim to specifying effects of cyclic voltammetric scan rates, scan time, temperatures and carbon addition on electrochemical sulphation of lead disk electrodes. Electrochemical transformation between solid Pb and solid PbSO4 was investigated by cyclic voltammetries (CVs) of Pb disk electrodes in aqueous H2 SO4, in line with the morphology change of electrodes before and after CV polarizations. Too rapid or slow scan rates tend to cause more irreversible sulphation. Long-duration cycling inevitably causes loss of active layer on the electrode surface and incurs more irreversible sulphation. Sulphation becomes more efficient and reversible at elevated temperature. Reversibility of sulphation of lead gets enhanced with the formation of more uniform and less crystalline particles. The irreversible sulphation became less with the addition of carbons (CNT or AB) in the electrolyte, due to lower polarizations upon carbon addition. The protocol of carbon addition is more effective at initial stage of cycling and becomes less effective at later stages. It is acknowledged that the improvement on long-term cycling remains a challenge, yet, which deserves further study.